Beyond Western Standards: Decolonial Perspectives on Religious and Cultural Dress Codes in South African Professional Environments - Mudau, Ndidzulafhi (E-Journal of Humanities, Art and Social Sciences (Online), 2025)
In post-apartheid South Africa, occupational attire regulations persist in embodying Western-centric norms that overlook indigenous and non-Western modes of religious and cultural expression through apparel. Although legislation advocates for workplace diversity, a significant disparity persists in policy and practice concerning the respect for diverse cultural and religious attire practices. This study, therefore, investigated the impact of colonial legacies on workplace dress codes and explored methods to decolonise professional attire policies better to represent South Africa’s cultural and religious diversity. The research examined multiple professional environments in South Africa, exploring the viewpoints of persons from diverse religious and cultural backgrounds. The study used a qualitative methodology, incorporating comprehensive interviews with employees, human resources managers, and policymakers. A decolonial theoretical framework analysed the impact of power structures and hierarchies on workplace dress codes. The study reveals conflicts between Western professional attire norms and traditional or religious garments, systemic obstacles to the expression of cultural and religious identity through clothing, diverse experiences of discrimination and marginalisation, effects on employee well-being and career progression, and effective incorporation of varied dress practices. The study underscores the imperative to decolonise workplace dress codes and establish inclusive policies that acknowledge and celebrate South Africa’s cultural and religious diversity. This study provides practical frameworks for businesses to develop culturally inclusive dress rules while questioning fundamental notions regarding “professional” attire. It enhances decolonial studies by examining how conventional workplace practices can either perpetuate or challenge colonial legacies. Keywords: Decolonial Theory, Workplace Attire, Religious Expression, Cultural Identity.